Damage Identification of RC Structures Using Wavelet Transformation. (2016) - Patel, S.S.; Chourasia, A.P.; Panigrahi, S.K.; Parashar, J.; Parvez, N.; Kumar, M.
Abstract: Vibration based techniques are gaining popularity for damage detection, precise localization and damage quantification. These techniques involve recording of the vibration signatures and their analysis for temporal and spectral characteristics to arrive at conclusive statement. Among different damage identification techniques, most of the algorithms are model based approaches and lacks standardization and accuracy. In this paper, feasibility of using output-only model-free wavelet based techniques for damage identification of 6-storied scaled reinforced concrete (RC) building is studied. The vibration signals at different floor levels of the RC building were acquired using wireless accelerometers. The vibration measurements were carried out for different cases i.e. bare frame and varying mass at different floors. The signal discontinuity of the acceleration response of RC building was extracted using complex continuous Gaussian wavelet transformation and analysed. The results show that wavelet coefficients are directly influenced by the change in physical properties of structure and are able to detect damage to a reasonable extent.